Population Pharmacokinetic Study of Gabapentin in Iranian Healthy Volunteers: Pop PK Study of Gabapentin in Iranian Healthy Volunteers - Kurd, Masoumeh; Esmaeili, Tayebeh; Derakhshandeh, Katayoun (Iranian Journal of Pharmaceutical Sciences, 2022)
The objective of the study was to evaluate the pharmacokinetics of a single oral dose of 300 mg gabapentin capsule in an Iranian healthy population. The study was a standard two-way, crossover, randomized, and single-dose study with one-week washout period in 24 healthy volunteers who received 300 mg gabapentin capsules (test and reference formulation). After drug administration, blood samples were taken according to the planned times over a period of 24 hours. The plasma concentrations of gabapentin were determined using the validated high-performance liquid chromatography (HPLC) method with ultraviolet (UV) detection. All the pharmacokinetic parameters for gabapentin in healthy volunteers were calculated using nonlinear mixed-effect modeling and standard non-compartmental methods. A one-compartment model with a first-order absorption rate and first-order elimination rate with a proportional error model described the pharmacokinetics of gabapentin. Values (relative standard error (RSE) %) for first-order absorption rate constant (Ka), oral clearance (Cl/F), and apparent volume of distribution (Vd/F) were 1.08 (7.23) 1/h, 6.72(0.29) L/h, and 73.82(5.10) L. The mean estimate for non-compartmental pharmacokinetic parameters including maximum plasma concentration (Cmax), the area under the curve to the last quantifiable concentration (AUCt), and the area under the curve to the infinity (AUCinf) was calculated. Cmax for test and reference formulation was 3850 ng/mL and 3856 ng/mL respectively. The AUCt for test and reference formulation was 39549 ng. h/mL and 40249 ng. h/mL respectively. The AUCinf for test and reference formulation was 47161 ng. h/mL and 633424 ng. h/mL respectively. The median (range) for the time to peak plasma gabapentin concentration (Tmax) for the test and reference drug was 3 (1.5-6) hours and 3 (1.5-5) hours respectively. The mean (standard deviation) elimination half-life (t1/2) of gabapentin for the test and reference drug was 9.39 (2.75) hours and 8.88 (2.48) hours. They were all within the acceptable range of 80-125%, consequently, we concluded that the two gabapentin formulations were bioequivalent. Our results confirmed that the gabapentin pharmacokinetic model in the Iranian healthy population was similar to other studied populations. However, we could not find any influential covariate to explain the inter-individual variability of parameters.